PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN DI PT. UKINDO BLANKAHAN MILL KAB.LANGKAT SUMATERA UTARA - Arini Zannah; Soulthan Saladin Batubara; Saimara A.M Sebayang (Jurnal Akuntansi dan Pajak, 2025)
PT. Ukindo Blankahan Mill, a company engaged in the palm oil industry and plantations, has faced a significant decline in performance and productivity, with production achievements falling short of company targets from 2021 to 2023. This decline in performance is influenced by various factors, including leadership style and employee compensation.This study aims to analyze the impact of leadership style and compensation on employee performance at PT. Ukindo Blankahan Mill. The research seeks to understand the extent to which these two factors contribute to improving employee performance and productivity.This study employs a quantitative approach with multiple linear regression analysis. Data were collected through surveys, observations, and documentation from 119 employees of PT. Ukindo Blankahan Mill, with a sample of 54 employees selected using stratified random sampling. The research instrument was a questionnaire measuring leadership style, compensation, and employee performance. Data were analyzed using validity and reliability tests, as well as classical assumption tests (normality, multicollinearity, heteroscedasticity) and multiple linear regression analysis.The study found that the leadership style variable was mostly valid with three significant indicators. However, the compensation variable did not show adequate validity for all tested items. Reliability tests indicated that the leadership style variable had acceptable internal consistency, while the compensation and employee performance variables showed low reliability. These findings underscore the importance of effective leadership style and compensation in enhancing employee performance, and highlight the need for improvements in the company’s compensation system.